My Baby Deserves Love, Not HIV: Enabling HIV-positive Indonesian Women to Access Prevention of Mother-to-Child Transmission of HIV Services - Najmah (Auckland University of Technology, 2020)
Getting married and having children is part of the social, cultural, and religious norms of Indonesian people, including those of women living with Human Immunodeficiency Virus (HIV). Pregnancies occur amongst these women. Unfortunately, only 10% of all pregnant women living with HIV, access Prevention of Mother-to-Child Transmission of HIV, or PMTCT services, annually. Without intervention, half of all babies born to mothers with HIV are at risk of contracting HIV through the mother’s pregnancy, delivery or from breastfeeding and three in four children’s deaths from Acquired Immunodeficiency Syndrome (AIDS) occurred before the age of five years. My research considers how to enable HIV-positive women to access PMTCT services, specifically focussing on heterosexually married mothers. I believe HIV-positive women are the real experts in terms of what they need to enhance their access to PMTCT services. My research allowed me to work with 18 HIV-positive women, 26 health workers, nine Non-Governmental Organisation (NGO) workers, and over 12 HIV policymakers through a series of focus group discussions, informal interviews, and visual methods. Three original theoretical contributions in this dissertation are the concept of marital deception, the concept of intersectionality and women’s vulnerability to HIV and the concept of HIV-related stigma or shame in the Indonesian context. My research shows that every Indonesian woman is at risk of HIV. HIV transmission is a complex issue, especially for mothers and wives within a patriarchal Islamic society. It is usually the man who contracts HIV through high-risk behaviours and passes it on to his wife, often with his knowledge, although sometimes unknowingly. After being confirmed as HIV positive, women may feel ostracised and resist accessing HIV care for fear of discrimination. The shame related to HIV means people may not talk about HIV within a family, community or even in health settings. Sadly, without HIV testing and intervention, a pregnant woman with HIV, therefore, her risk being unaware of her own HIV status and may risk HIV transmission to her child. This research reveals intersected barriers to accessing PMTCT services and indicates the need for holistic solutions to enhance accessibility to these services to reduce HIV risk to an estimated 30 babies at risk of HIV every day in Indonesia. This thesis has provided deeper insights into Feminist-Participatory Action Research (FPAR) as an important methodology to create a safe collective space for marginalised women and reveal factors that enable HIV-positive women to access PMTCT, such as the acknowledgment of wives and mothers at risk of HIV and the need to accommodate the socio-cultural and moral contexts of women’s lives within PMTCT programmes. This study will be the beginning of ongoing research into women’s participation in HIV programmes and HIV policy development and inspire further research. By producing audio-visual materials, the women’s aspirations can travel visually and verbally and act as influence on the provision of appropriate access to PMTCT services.
Keywords: HIV; PMTCT; Aspiration; Trust; Participation; Feminist-participatory action research; Indonesian women